Intensity of contact with frontline workers and its influence on maternal and newborn health behaviors: cross-sectional survey in rural Uttar Pradesh, India - Tanica Lyngdoh; Sutapa B. Neogi; Danish Ahmad; Srinivasan Soundararajan; Dileep Mavalankar (BMC, 2018)
Abstract Background India is committed to improving maternal and newborn health in order to achieve the targets for India's Millennium Development Goal 4. Considering their role as a link between community and health systems, frontline workers (FLWs) can be effectively utilized in strengthening maternal and newborn care. In this paper, we set out to examine the effect of intensity of contact with FLWs on key maternal and newborn health behaviors and to determine if this association varies by status of Self Help Group (SHG) membership. Methods This population-based cross-sectional study included 2208 currently married women aged 15-49 years who had delivered a baby during the last 15 months prior to the survey and selected through a multi-stage cluster sampling from rural villages and urban wards. The outcome of interest included variables related to key knowledge and practice of healthy behavior in relation to maternal and newborn health and exposure variable considered was intensity of contact with FLWs. Results Of the women interviewed, 1729 (78%) belonged to SHG household. For knowledge on the need for at least 3 antenatal care (ANC) check-ups, two tetanus toxoid (TT) injections and consumption of 100 or more iron-folic acid (IFA) tablets, proportion of those who were aware of these practices increased with increasing number of contacts with FLWs (P value < 0.001). Practice for TT injections showed an increasing trend with increasing number of contacts with FLW. An increase in the odds of delivering in an institution was observed in those who had higher number of contacts as compared to those with no contacts (P value < 0.001). With regard to newborn healthy behavior practice, breastfeeding within 1 h of delivery showed significant association and the odds of this practice improved in those who had ≥ 3 contacts with FLW as compared to those had no contacts. Except for consumption of 100 or more IFA tablets, there was no interaction of these associations by SHG status. Conclusion There was an overall low prevalence of both knowledge and practice of key maternal and newborn healthy behaviors and only a few of these were associated with frequency of contacts with FLW. Findings not only highlight the urgent need for effectively leveraging FLWs to strengthen maternal and newborn care but also to improve the quality of services provided by them.